The Behavior of Non-Oil Commodity Prices - Borensztein, Eduardo (Occasional Papers; Occasional Paper ;, 1994)
This paper analyzes global commodity trends and concludes that the marked decline in real commodity prices of the past decade should be regarded as largely permanent and irreversible. The authors contend that the analysis of commodity prices should be extended to include the role of the breakdown of major international commodity agreements. In addition, the authors analyze how developments in the former Soviet Union have affected commodity supply conditions.